2013
DOI: 10.21432/t25p4z
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Views: Exploring the Potential for Technology Integration in Early Childhood Education Programs / Changement d’opinion: Exploration du potentiel d’intégration de la technologie dans les programmes d’éducation de la petite enfance

Abstract: Using technology with children in play-based early learning programs creates questions for some within the Early Childhood Education (ECE) community. This paper presents how two faculty who teach in ECE-related degree programs integrated educational technology into their teaching pedagogy as a way to model to their students how it can be used to support children’s play and learning opportunities. The authors identify how collegial dialogue helped them to use various technologies and social media in their teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Once we have a better understanding of the reasons, more efforts would be needed to help these teachers overcome barriers to effective use of such strategies. One way to support these teachers is to help them integrate technology into some relatively "old-fashioned" strategies (Bahng & Lee, 2017;Dietze & Kashin, 2013). For example, research shows that virtual manipulatives can be as effective as physical manipulatives (Satsangi et al, 2016;Moyer-Packenham et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Once we have a better understanding of the reasons, more efforts would be needed to help these teachers overcome barriers to effective use of such strategies. One way to support these teachers is to help them integrate technology into some relatively "old-fashioned" strategies (Bahng & Lee, 2017;Dietze & Kashin, 2013). For example, research shows that virtual manipulatives can be as effective as physical manipulatives (Satsangi et al, 2016;Moyer-Packenham et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, classical research studies have revealed that human newborns, even just a few days old, displayed brain activity that mirrored that of the adults they were observing (Nadel, 2015). Additionally, children under the age of two exhibited the ability to accurately anticipate the goals of another person’s actions (Dietze & Kashin, 2013). These findings suggest a brain mechanism even in initial development that is closely related to action observation and execution (Gallese et al, 2013).…”
Section: Introductionmentioning
confidence: 99%